2008
DOI: 10.2741/2783
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow changes in acute subarachnoid hemorrhage

Abstract: Delayed vasospasm and secondary injury due to ischemia occur frequently in the setting of subarachnoid hemorrhage (SAH), and these changes have been well characterized within the last decades. Considerable effort has also been put into the development of therapeutic strategies and appropriate monitoring modalities. However, although in particular acute injury is known to contribute significantly to overall outcome in SAH, these immediate alterations still remain largely neglected in current research. Few studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…In the early phase of SAH, brain injury has been discussed to take place via apoptotic pathways, induced by the sudden rise of intracranial pressure and the subsequent impairment of the cerebral perfusion. Several downstream pathways of this concept have been described within the past years [16,27,29,47,56,60,61,71,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early phase of SAH, brain injury has been discussed to take place via apoptotic pathways, induced by the sudden rise of intracranial pressure and the subsequent impairment of the cerebral perfusion. Several downstream pathways of this concept have been described within the past years [16,27,29,47,56,60,61,71,73].…”
Section: Discussionmentioning
confidence: 99%
“…Direct brain injury in the early phase starts with the onset of the bleeding and is mediated mainly through physical stress. A rise in intracranial pressure (ICP) leads to a decrease in cerebral perfusion, which can induce hypoxia [40,61]. Furthermore, blood elicits a deleterious effect on the brain parenchyma, leading to a swelling of the brain within the first days after SAH.…”
Section: Introductionmentioning
confidence: 99%
“…Rapidly increased intracranial pressure after SAH leads to significantly decreased regional cerebral blood flow (rCBF) and metabolic changes (Doczi 1985;Schubert and Thome 2008). Acute brain injury following SAH is a key factor related to the poor prognosis (Broderick et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A more pronounced initial decrease in CBF has also been found in patients with a higher Hunt and Hess grade (5,12,19). Acute hypoperfusion is caused by various cellular and structural changes, but the theory that acute vasospasms are a major factor has gained widespread acceptance (20). A retrospective analysis of a large multicenter trial has also shown angiographically that acute vasospasms within the first 48 hours occur in 10% of patients admitted for SAH treatment (2,16,22).…”
Section: Hemodynamic Changes After Subarachnoid Hemorrhagementioning
confidence: 96%
“…This early and profound change in perfusion is thought to reflect the impact of the primary injury and vulnerability to secondary insults (20). Also, the initial severity of the hemorrhage and CBF reduction during the early SAH period are the major determinants of imminent morbidity and mortality (3,17).…”
Section: Hemodynamic Changes After Subarachnoid Hemorrhagementioning
confidence: 99%